Young patients with divergence insufficiency related to excessive near work. (2nd July 2020) - Xia, Yu; Cao, Liqun; Peng, Xiujun; Wang, Lejin
ABSTRACT: The purpose of this study is to explore the relationships between excessive near work and divergence insufficiency esotropia in young adults. A prospective study described a series of young patients with divergence insufficiency esotropia related to excessive near work between 2012 and 2017. The medical records of twelve young patients with divergence insufficiency esotropia and a history of excessive near work were reviewed, and the duration of near work, angle of primary position deviations at distance and at near, and angle of primary position deviations after refraining from near work for 3 months were analyzed. All patients with divergence insufficiency esotropia (age range: 21–35 years) showed an initial esodeviation ranging from 18 to 35 prism diopters for distance fixation and ranging from 8 to 20 prism diopters for near. Neurological evaluation in all cases was normal. Myopic refractive errors were detected in twelve patients. Every patient persisted near work for more than 6 h a day over a period of several months (minimum 4 months). Reductions in esodeviation were noted in twelve patients after refraining from near work for more than 3 months. Only one patient was diplopia free in all positions of gaze. The remaining eleven patients were treated successfully, six with prisms and five with surgery. They were all orthophoric and demonstrated restored binocularity at the post-treatment examinations. Our findings suggested that excessive near work might influence the development of divergence insufficiency esotropia in young adults. Refraining from excessive near work could decrease the degree of esodeviation in these patients.